Environmental-Based Public Service Innovation, QRIS and VA in Bandung - Setiadin; Imas Sumiati (The Indonesian Institute of Science and Technology Research, 2022)
In the midst of the current COVID-19 pandemic, it is uncertain when it will end. This certainly affects the realization of tax revenues in 2020. This unstable economic condition affects many aspects. The company's turnover has decreased, people's income has decreased, job opportunities have decreased, the education level of the community is difficult to reach due to the absence of education costs. This pandemic that has hit Indonesia has an impact on the policy ecosystem that has been running previously, one of which is the policy in paying taxes. This is related to the economic situation that is also affected by the pandemic. The Bandung City Regional Revenue Management Agency sees this phenomenon. BAPENDA Bandung City innovates how to make people pay taxes from waste. In the end, BAPENDA collaborated with Bank Waste, Bank Mandiri, and Bank BJB to initiate the innovation. Through this collaboration, Bank Mandiri will act as a waste manager, and Bank BJB will play a role in financial management.